Development of KOIN Mobile Learning to Prevent Student Misconceptions on Chemical Bonding Material - Oktaviani, Lestari Rachma; Sukarmin, Sukarmin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Chemistry is a relatively tricky science; thus, it must be studied in depth to avoid misconceptions. These misconceptions can be caused by students themselves, teachers, textbooks, material context, and teaching methods. One way to prevent misconceptions is by using learning media that is easy for students to understand. Field facts indicate that chemistry teaching in high schools is still conducted conventionally, and only a few students understand the concepts of chemical bonding. Mobile learning is an interactive multimedia that can enhance students' learning motivation. This research aims to determine the feasibility of using KOIN m-learning to prevent student misconceptions about covalent and ionic bonds. The feasibility of m-learning is reviewed from two aspects: validity and practicality. This study employs the Research and Development (R&D) methodology, utilizing the development model proposed by Sukmadinata. The limited trial was conducted in class XI-MEDITEK of SMA Ta'miriyah Surabaya, with 15 students selected based on the most significant number of students who did not understand concepts in the pretest results. The research data shows that (1) KOIN m-learning is declared valid as indicated by the content validity mode of 4 with category valid and construct validity mode of 4 with category valid, (2) KOIN m-learning is declared practical as indicated by the average results of the student response questionnaire, supported by observations of student activities, of 97.04% with category highly practical, The results indicate that KOIN m-learning is feasible to be used to prevent student misconceptions about chemical bonding material.